ENHANCING THE EFFECTIVENESS OF COLLABORATION STRATEGIES IN DEVELOPING STUDENTS’ INDEPENDENT AND TEAMWORK SKILLS BASED ON THE ACTIVITY APPROACH - Xafizov Xikmatillo Usmonovich (New modern researchers: modern proposals and solutions, 2025)
This article explores the methodological foundations and practical solutions for enhancing the effectiveness of collaboration strategies aimed at developing students' independent and teamwork skills within the framework of the activity-based approach in education. The activity-based approach focuses on organizing learning as an active, meaningful process where students engage in solving tasks individually and in collaboration with peers. The study analyzes the nature of collaboration strategies, their formation mechanisms, and implementation methods in educational practice. The effectiveness of such strategies is linked to the development of communicative competence, critical thinking, and leadership qualities in students.